Groups of friends as a strategic vector for museums - Ribeiro, Sofia (Revista Comunicando, 2015)
The goal of this paper is to analyse how “museums friends groups” can be a strategic vector for museums in order to attract the public attention.?The museum spaces have been in continuous progress and nowadays they face new challenges. In many cases, the museums are acknowledging cultural memberships associations as a source for their revitalization. The present work focuses on museum friends groups (GAM) as an essential key for museums, given that they may find answers for the needs of the public’s and of stakeholders’ expectations. Nowadays, friends groups face new challenges: besides their traditional tasks in touting new art pieces and sponsors, they have a role in attracting the public’s attention, a public that each day is becoming more diverse. These groups may thus have a crucial role in society; due to their contribution, the access to culture can be more widespread.